The Baby-sitters Club. 7, Boy-crazy Stacey - Martin, Ann M; Galligan, Gale (New York, NY Graphix, an imprint of Scholastic, 2019)
"Stacey and Mary Anne are baby-sitting for the Pike family for two weeks at the New Jersey shore. Things are great in Sea City: There's a gorgeous house right on the beach, a boardwalk, plenty of sun and sand... and the cutest boy Stacey has ever seen! Mary Anne thinks that Stacey should leave Scott alone and focus on the Pike kids, but Stacey's in love. Looking for reasons to hang around his lifeguard stand takes up all of her time, which means Mary Anne has to do the job of two baby-sitters. Mary Anne doesn't like it one bit! How can she tell Stacey that Scott just isn't interested without ruining their friendship and breaking Stacey's heart?"--Provided by publisher
Comic strips
2
Keywords: Babysitters -- Comic books, strips, etc; Clubs -- Comic books, strips, etc